2013
DOI: 10.3892/mmr.2013.1539
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral-mediated p38 MAPK RNAi attenuates aldosterone-induced myocyte apoptosis

Abstract: Abstract. Aldosterone-induced myocyte apoptosis is an important component of cardiovascular disease. While the p38 mitogen-activated protein kinase (p38 MAPK) pathway has been shown to be crucial in myocyte apoptosis, whether aldosterone induces myocyte apoptosis through this pathway remains unclear. In the present study, three individual strands of p38 MAPK short hairpin RNA (ShRNA), delivered by lentiviral vectors (PGLV), were constructed and used to explore the role of p38 MAPK pathway activation in aldoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…Studies have revealed that aldosterone directly induces myocyte apoptosis through the p38 MAPK signaling pathway, which in turn exerts a protective effect on aldosterone-induced myocyte apoptosis. 44 Activation of the p38 MAPK signaling pathway can induce myocardial cell apoptosis, which is consistent with the findings of the present study. Therefore, the p38 MAPK signaling pathway is potentially the pathway associated with promotion of cardiomyocyte apoptosis in a rabbit susceptibility model of hyperthyroidism-induced AF following sympathetic activation.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have revealed that aldosterone directly induces myocyte apoptosis through the p38 MAPK signaling pathway, which in turn exerts a protective effect on aldosterone-induced myocyte apoptosis. 44 Activation of the p38 MAPK signaling pathway can induce myocardial cell apoptosis, which is consistent with the findings of the present study. Therefore, the p38 MAPK signaling pathway is potentially the pathway associated with promotion of cardiomyocyte apoptosis in a rabbit susceptibility model of hyperthyroidism-induced AF following sympathetic activation.…”
Section: Discussionsupporting
confidence: 93%
“…Knockdown of Prx V expression in HT22 cells enhanced glutamate-induced decreases in cell viability and increased cellular apoptosis, which may be associated with increases in the cellular ROS levels. The MAPK signaling pathway is widely involved in cell proliferation, migration, apoptosis and differentiation, and has been reported to be closely associated with cellular ROS levels (35)(36)(37). However, to the best of our knowledge, no previous evidence has demonstrated an association between Prx V and MAPK in neuronal cell apoptosis.…”
Section: Discussionmentioning
confidence: 89%
“…The role of p38 in cancer depends on the cell type and cancer stage. Certain studies have reported that p38 increases cell proliferation, whereas in others, the activation of the MAPK p38 pathway is described as tumor suppressive (29)(30)(31)(32)(33)(34). In the present study, the p38 pathway was observed to exhibit a tumor suppressive role in HCC.…”
Section: Discussionmentioning
confidence: 99%